2018
DOI: 10.1002/bit.26513
|View full text |Cite
|
Sign up to set email alerts
|

Thermoactivation of a cellobiohydrolase

Abstract: We have measured activity and substrate affinity of the thermostable cellobiohydrolase, Cel7A, from Rasamsonia emersonii over a broad range of temperatures. For the wild type enzyme, which does not have a Carbohydrate Binding Module (CBM), higher temperature only led to moderately increased activity against cellulose, and we ascribed this to a pronounced, temperature induced desorption of enzyme from the substrate surface. We also tested a "high affinity" variant of R. emersonii Cel7A with a linker and CBM fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
(61 reference statements)
3
5
0
Order By: Relevance
“…4 ), and the ranking of the performance of the enzymes was similar at the two reaction temperatures. The lack of increase in hydrolytic rate by cellulases in Cellic ® CTec3 with temperature (Q 10 close to 1 between 30 and 50 °C) is in agreement with data published by Westh et al [ 39 , 40 ] who showed that at low Avicel concentrations reduction in substrate affinity caused by heating (increase in K M ) cancels thermoactivation (increase in k cat ). In the present study, the substrate concentration was low (2% DM ~ 1% cellulose).…”
Section: Resultssupporting
confidence: 92%
“…4 ), and the ranking of the performance of the enzymes was similar at the two reaction temperatures. The lack of increase in hydrolytic rate by cellulases in Cellic ® CTec3 with temperature (Q 10 close to 1 between 30 and 50 °C) is in agreement with data published by Westh et al [ 39 , 40 ] who showed that at low Avicel concentrations reduction in substrate affinity caused by heating (increase in K M ) cancels thermoactivation (increase in k cat ). In the present study, the substrate concentration was low (2% DM ~ 1% cellulose).…”
Section: Resultssupporting
confidence: 92%
“…However, these considerations do not account for the full difference with the SEE results. The dissociation k off value computed here (0.79 s −1 ) is on par with single-molecule tracking experiments of TrCel7A (k off = 0.1 to 0.2 s −1 ) (18, 31), with the higher temperature in our simulation potentially accelerating dissociation, as has been speculated for related cellulases (47). Of note, the computational k cat value of 6.9 s −1 (details are in SI Appendix) is well in line with the k cat values measured not only by HS-AFM (29,48) but also, by different biochemical methods (15-17, 28, 32).…”
Section: Discussionsupporting
confidence: 84%
“…As already stated, the high/low values of substrate loads are well above/below K M for both Avicel and pNPL, and the data therefore reasonably represent the limiting cases. This interpretation is further supported by published binding parameters for the same enzyme–substrate systems (Badino, Kari, Christensen, Borch, & Westh, ; Schiano‐di‐Cola et al, ; Westh et al, ), which suggests almost complete adsorption of enzyme (85–98% bound) at high Avicel load (90 g/L). We used nonlinear regression analyses to fit the pH curves as detailed in the Supporting information.…”
Section: Discussionsupporting
confidence: 63%